Pelaksanaan Pembinaan Narapidana Menurut Undang Undang Nomor 12 Tahun 1995 Tentang Pemasyarakatan Untuk Mencegah Pengulangan Tindak Pidana (Studi Di Lembaga Pemasyarakatan Kelas II A Pematang Siantar) - Rudi Fernando Sianturi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
He main purpose of the Correctional Institution is to provide guidance for inmates based on the institutional system, and the method of coaching as the final part of the criminal justice system and criminal justice system.In the formulation of Article 1 number 1 of Law Number 12 of 1995 concerning Corrections, it is explained that "Penitentiary is an activity to carry out fostering of color based on the system, institution and method of coaching which is the final part of the criminal justice system in the criminal justice system". And in Article 1 number 2 of Law Number 12 of 1995 concerning Corrections, it is stated: Correctional Institutions, hereinafter referred to as LAPAS, are places to carry out the development of prisoners and correctional students.The implementation of imprisonment with the correctional system refers to Law Number 12 of 1995. Correctional institutions in the criminal justice system are included in the ranks of law enforcement officers who are members of the integrated criminal justice system. Keywords: Crime, Corruption, Money Laundring.The position of Correctional Institutions as law enforcers is explicitly confirmed in Article 8 of Law Number 12 of 1995, which states that: "Penitentiary officers are law enforcement functional officials who carry out duties in the field of coaching, securing and guiding correctional inmates.Keywords: Crime, Corruption, Money Laundring